Improving Rutting Resistance of Pavement Structures Using Geosynthetics: An Overview. (8th January 2014) - Mirzapour Mounes, Sina; Karim, Mohamed Rehan; Khodaii, Ali; Almasi, Mohammad Hadi
Abstract : A pavement structure consists of several layers for the primary purpose of transmitting and distributing traffic loads to the subgrade. Rutting is one form of pavement distresses that may influence the performance of road pavements. Geosynthetics is one type of synthetic materials utilized for improving the performance of pavements against rutting. Various studies have been conducted on using different geosynthetic materials in pavement structures by different researchers. One of the practices is a reinforcing material in asphalt pavements. This paper intends to present and discuss the discoveries from some of the studies on utilizing geosynthetics in flexible pavements as reinforcement against permanent deformation (rutting).